Beyond ethical dilemmas: improving the quality of end-of-life care in the intensive care unit - Rubenfeld, Gordon D (BioMed Central, 2003)
Consensus guidelines on providing optimal end-of-life care in the intensive care unit (ICU) are important tools. However, despite 30 years of ethical discourse and consensus on many of the principles that guide end-of-life care in the ICU, care remains inadequate. Although consensus on the most challenging ethical aspects of some cases will remain elusive, this need not deter clinicians from engaging in practical quality improvement, best practice, and educational interventions to provide compassionate care to all critically ill patients, including those who ultimately die.